CODE-SWITCHING IN DISNEY'S ENCANTO (2021): Exploring Types and Functions in Movie Contexts - Muhammad Aliansyah Ramadhan, - (Universitas Pendidikan Indonesia, 2023)
This research focuses on the phenomenon of code-switching in the Disney movie Encanto (2021), examining the types of code-switching and their functions within the English and Spanish languages. Code-switching, the mixing of languages or linguistic types within a conversation, is common in bilingual and multilingual societies. The study aims to enhance insights into various code-switching types and their purposes in movie situations and casual conversations. It is valuable for sociolinguistic readers to explore code-switching types, functions, and causes. The study used a qualitative method to analyze the use of code-switching in the movie, which used Poplack's (2001) theory to examine the types of code-switching and used function of code-switching theory by Appel and Muysken (2006) to determine its functions. The data were gathered by downloading the movie and watching it while reading the screenplay from an online source, followed by data analysis and categorization of code-switching occurrences based on established theories. The findings reveal that the characters in Encanto (2021) primarily engaged in two types of code-switching: tag-switching and intra-sentential switching. Tag-switching involves inserting words or phrases from one language at the beginning of an utterance. In addition, intra-sentential switching occurred when a sentence incorporates a different language. This study shows that 64 instances of code-switching occurred in the movie, with equal occurrences of 50% (32 occurrences) of tag-switching and intra-sentential switching. However, inter-sentential switching was not found in this movie, where complete sentences were switched between languages.